Para que lado correr? Bem-estar do trabalhador, comportamento de cidadania organizacional e conflito trabalho-família - Gomes, Tarízi Cioccari (2022)
The employee well-being is a complex phenomenon which involves the perception of his or her work environment, social relationships and behaviors between colleagues and managers, besides family involvement and interactions. Feeling good, helping co-workers voluntarily and keeping the balance between work-life and home environment are great challenges, which are indispensable and interdependent in order to maintain the mental health of the employees. The general objective of this thesis was to propose a theoretical-empirical model based on the understanding of how Organizational Citizenship Behaviors (OCB), Employee Well-Being (EWB) and Work-Family Conflict (WFC) are related, from the perspective of federal civil servants who work in Federal Institutes and Federal Technical Schools in Rio Grande do Sul. The theoretical framework covered General Well-Being, both at Work and Employee, OCB and WFC themes. The research is quantitative, with the application of the Employee WellBeing Scale by Pradhan and Hati (2019), the Organizational Citizenship Behavior Scale by Bastos, Siqueira and Gomes (2014) and the Multidimensional Work-Family Conflict Scale by Carlson, Kacmar and Williams (2000), validated in Brazil by Aguiar (2016). It’s also a qualitative research, with semi-structured interviews with civil servants. 721 civil servants participated in the quantitative research, and in the qualitative research 13 servants participated online. For the analysis of quantitative data, the SPSS software and its complement AMOS Graphics were used, and for the analysis of the interviews, ATLAS.ti Version 9 was used, based on Content Analysis (BARDIN, 2016). Exploratory Factor Analysis, Confirmatory Factor Analysis and Structural Equation Modeling were performed. The sample covered mostly married women, with children and a high level of education. The research results identified that the Employee Well-Being Scale (EWBS) is composed of well-being related to feelings and perceptions of life, social and collaborative well-being, and belonging and decision-making well-being. The research presented evidence of validation of EWBS, formed by 14 items, which showed converging and discriminating validity, just as all satisfactory indicators, and 17 variables were excluded from the original model. Three proposed hypotheses were confirmed, as well as the theoretical-empirical model was developed and presented. It is concluded that the OCB positively influence the EWB, the OCB negatively influence the WFC, and the WFC negatively influence the EWB. It was thus perceived the significant relationship between the constructs and the need to promote policies and institutional tools that contribute to the practice of OCB among co-workers, engaging the servants, through greater collaboration and greater support among colleagues, thereby favoring the reduction of conflicts at work and consequently at home, with repercussions on the improvement of the EWB.